Study on Hybrid Project Management Implementation in the Construction Industry - Abu Bakar, Masitah; Kasim, Narimah; Fathi, Mohamad Syazli (Research in Management of Technology and Business, 2023)
Project management is one of the part in construction industry where it requires managing every stage of the project’s life cycle, from conceptualization to completion of the project. However, in the construction project management, the increasing of material price, severe weather and other external problems has a number of consequences that lead to cost and time overruns, disputes, and project failure. Problems that arise during on-site production is a difficulty that caused by the construction project supply chain, inadequate project management and poor performance. This study on hybrid project management was conducted to identify the potential, key criteria and the strategies of hybrid project management implementation as they can be the new method in improving the activities in construction industry. In order to achieve the objectives, this research was conducted using qualitative method for primary data collection and gathering information from many sources such as books, journals, and articles as secondary data. Furthermore, semi-structured interview was conducted from four (4) respondent of G7 Contractors registered under CIDB and the focus spot was in Selangor area as primary data. Then, the data was analysed using content analysis to provide data information related in the hybrid project management from the respondents. The significant finding for the potential of hybrid project management is workplace culture, as for key criteria is software design and the strategies to implement hybrid project management were knowledge, develop solutions, also proposed and improved management. In conclusion, this research contributes to a better understanding of the uses of hybrid project management as it can be implemented in construction industry.